2010
DOI: 10.1016/j.biopsych.2010.01.021
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Basal Ganglia Dysfunction and Conversion to Psychosis: Neurocognitive Deficits and Dyskinesias in the Prodromal Period

Abstract: Background-Movement abnormalities and cognitive deficits may represent external markers of an underlying neural process linked with the early etiology of psychosis. As basal ganglia function plays a governing role in both movement and cognitive processes, an understanding of the relationship between these phenomena stands to inform etiological conceptualizations of vulnerability and psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
83
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 71 publications
4
83
2
Order By: Relevance
“…42 In support of this theory, prospective investigations in youth with prodromal syndromes have observed that the presence of specific motor abnormalities significantly increases the odds of developing psychosis in a brief 2-year period. 10,43 In a new exciting direction, some work also suggests that cerebellar-specific motor behavior (i.e., balance) may also have unique predictive value for negative symptoms as well. 29,44 This series of findings has significant practical use for the refinement of risk calculators 45 as well as efforts to understand unique potential subtypes.…”
Section: At Issuementioning
confidence: 99%
See 1 more Smart Citation
“…42 In support of this theory, prospective investigations in youth with prodromal syndromes have observed that the presence of specific motor abnormalities significantly increases the odds of developing psychosis in a brief 2-year period. 10,43 In a new exciting direction, some work also suggests that cerebellar-specific motor behavior (i.e., balance) may also have unique predictive value for negative symptoms as well. 29,44 This series of findings has significant practical use for the refinement of risk calculators 45 as well as efforts to understand unique potential subtypes.…”
Section: At Issuementioning
confidence: 99%
“…8,9 Indeed, if schizophrenia is a disorder characterized by domains of symptoms as well as cognitive and emotive deficits spanning a host of disparate mechanisms and structures, then perhaps these circuits, responsible for dynamic communication with frontal areas, may be a good target for explaining this heterogeneity. 10 Although theories have pointed to this idea in the past, 11,12 sophisticated cross-disciplinary empirical work is now filling in the missing pieces. One of the most exciting developments in this area focuses on new evidence suggesting direct 2-way communication between the basal ganglia and the cerebellum, independent of the cortex.…”
mentioning
confidence: 99%
“…Motor dysfunction in psychosis populations varies greatly and includes relatively diffuse neurological soft signs (Mittal et al 2014), dyspraxia (Schiffman et al 2015), postural control deficits (Marvel et al 2004; Bernard et al 2014), and both hypo- and hyper-kinesias (Mittal et al 2010; Pappa & Dazzan 2009), catatonia and psychomotor slowing (Walther & Strik 2012), and motor learning deficits (Marvel et al 2007). What is particularly interesting is that in psychosis risk populations where confounds such as drug abuse and medications are less prevalent, movement abnormalities have been useful in predicting symptom course and disease progression (Dean et al .…”
Section: Motor Dysfunction Across Disordersmentioning
confidence: 99%
“…Critically, in many cases motor systems dysfunction is present in the absence of medication (Caligiuri & Lohr 1994; Fenton et al 1994), indicating that these deficits are not merely a side effect of pharmacological treatments. Furthermore, evidence also indicates that motor systems dysfunction is present prior to disease onset (e.g., Mittal et al 2010). Together this suggests that it may be a trait feature of psychopathology, though it is likely that there are state effects with respect to the severity of this dysfunction associated with disease course, symptom severity, and medications.…”
mentioning
confidence: 99%
“…The negative finding in Southeast Asians suggests an ethnicity effect [59]. In addition, spontaneous abnormal movements were reported in schizophrenia spectrum disorders and prodromal states [60,61,62,63], suggesting that the vulnerability for schizophrenia was associated with these movement disorders [11,62]. …”
Section: Clinical Perspectivesmentioning
confidence: 99%